EVALUASI PELAKSANAAN KEGIATAN KULIAH KERJA KESEHATAN MASYARAKAT (K3M) DI KECAMATAN SAMIGALUH KABUPATEN KULON PROGO - , SUNIAWAN SATRIO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: K3M or Kuliah Kerja Kesehatan Masyarakat was a program held by Faculty of Medicine Gadjah Mada University. This program was the equivalent of Kuliah Kerja Nyata Program Pemberdayaan Masyarakat (KKN PPM) which is held by Gadjah Mada University. The evaluation of K3M activity is important so that we could find out the effectiveness of the program or what were the positive and negative impact of the activity on the students who carried out the activity and the community where the activity was held. The results of this evaluation could be used for an instrument by the Faculty of Medicine GMU to consider whether we should continue or recreate this program in the future. Objective: This research was done in order to evaluate the Kuliah Kerja Kesehatan Masyarakat (K3M) program in Kecamatan Samigaluh, Kabupaten Kulon Progo. Method: This research used qualitative method with the output being descriptive explanation. The datas were obtained from the community health problem solving report of K3M program in Kecamatan Samigaluh, Kabupaten Kulon Progo. Result: all of the report were complete. There were a small portion of the problem solving report that not match between theme and the content. In addition, suggestion or recommendation on the report were less appropriate because they were aimed at the people where the student wouldn't be able to follow up if there were/were no changes in the community. The students' role as a doctor were also less noticeable by observing the reports because most of the researches and problem solving activities done in the process were only promotive. Conclusion: Recommendation for Faculty of Medicine GMU as the organizer of the K3M program is needed so that they support and facilitate the implementation of the problem solving program with the intention to improve the effectiveness. On the other hand, the reporting system needs to be reconsidered because it didn't reflect the role of the students as a primary health care doctor. Keywords: Kuliah Kerja Kesehatan Masyarakat, Evaluation, Community Health Problem Solving Report.